2011 IEEE Global Engineering Education Conference (EDUCON) 2011
DOI: 10.1109/educon.2011.5773111
|View full text |Cite
|
Sign up to set email alerts
|

Designing an interactive multimedia learning system for the children of primary schools in Jordan

Abstract: Abstract-With the introduction of the Internet, and several new inventions and technologies especially in the communication and computer systems' field, there is a need to enhance teaching and educational methods through the utilization of those technologies which may improve the abilities of educators to present information in an interactive and media enhanced formats relative to traditional methods. This may help students or learners through offering them the information in channels and methods that can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…Using interactive multimedia in the teaching process is growing in the present context. Interactive learning plays a very important role in assisting students in learning processes [6]. It has possibility to enhance the early education system with multimedia technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using interactive multimedia in the teaching process is growing in the present context. Interactive learning plays a very important role in assisting students in learning processes [6]. It has possibility to enhance the early education system with multimedia technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beberapa hasil penelitian relevan yang mendukung berhasilnya pembelajaran dengan multimedia antara lain penelitian yang dilakukan oleh Nusir, S (2010). Hasil penelitian ini menunjukkan bahwa multimedia interaktif dapat memperbaiki keterampilan peserta didik dalam belajar dan memberikan alternatif yang sangat berguna untuk menggantikan metode tradisional.…”
Section: Pendahuluanunclassified
“…According to (Nusir et al, 2011, p. 49) "Students who have visual, or hearing problems may not be able to see or hear well the class material especially when class size is large." However, schools and colleges should adopt a new way of teaching, which make their students enjoying the lesson and more active, Nusir et al (2011) were reported "new technologies can provide a solution to this problem by recording different teacher courses or through an e-learning system. A new interactive educational system may provide solutions to the problems in the traditional educational systems" (p. 49).…”
Section: Introduce the Problemmentioning
confidence: 99%